1981
DOI: 10.1063/1.328772
|View full text |Cite
|
Sign up to set email alerts
|

Sodium passivation in Al-SiO2-Si structures containing chlorine

Abstract: Experiments have been done to measure the trapping and neutralization kinetics of sodium ions in Al-SiO2-Si structures using oxides grown with HCl-Ar/O mixtures. The trapping of sodium at the Si-SiO2 interface was quantified by thermally stimulated ionic current (TSIC) measurements made at negative applied electric fields following positive bias temperature stress. There were three distinct types of behavior depending on the chlorine content of the oxide. For chlorine contents ≳3.0×1015 atoms cm−2 the TSIC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…Chlorine incorporation.--The results for the total chlorine incorporated as a function of time or HC1 concentration are generally consistent with those previously reported (2,5,8). However, a rapid increase in the so-called "threshold" region is not apparent as in our earlier results (2).…”
Section: Initial Oxide Thickness (Nm)supporting
confidence: 91%
See 2 more Smart Citations
“…Chlorine incorporation.--The results for the total chlorine incorporated as a function of time or HC1 concentration are generally consistent with those previously reported (2,5,8). However, a rapid increase in the so-called "threshold" region is not apparent as in our earlier results (2).…”
Section: Initial Oxide Thickness (Nm)supporting
confidence: 91%
“…According to these authors, the samples belonging to the agglomerated phase regime contain C1 higher than 3 • 10'5/cm 2 for all the oxidation temperatures (5). However, in addition to the agglomerates we have observed individual particle microstructures for samples with C1 content higher than 3.0 x 1015/cm 2.…”
Section: Initial Oxide Thickness (Nm)mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, the values of calculation parameters-the potential well depth ͑0.5 eV͒ and the preexponential factor in the expression for jump probability (10 6 s Ϫ1 )-are not in agreement with previously reported data for activation energy of ion mobility 9 and oscillation frequency of ions in the potential well ͑ϳphonon frequency͒. 18,19 The qualitative form change for the quasistatic capacitance-voltage (C -V) characteristics caused by sample polarization is direct evidence of significant ion neutralization at the SiO 2 /Si IF. After ion move to IF the C -V curve essentially spreads ͑Fig.…”
Section: Thermostimulated Depolarizationcontrasting
confidence: 52%
“…Actually depending on the experimental technique used by various authors the observed results are ascribed to the effect of free ion drift ͑transit-time experiments, 9,10 dynamic currentvoltage (I -V) characteristics͒, [11][12][13][14][15] or as the manifestation of ion trap emptying ͑isothermal or thermostimulated polarization and depolarization of insulator͒. [16][17][18][19][20][21] The influence of semiconductor electrons on the ion migration in the insulator has not been considered at all. Opposing opinions have been reported concerning the ion neutralization possibility, owing to electron capture from the semiconductor on traps formed by ions and their dielectric environment.…”
Section: Introductionmentioning
confidence: 94%